2022
DOI: 10.1002/jcla.24784
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features, prognostic significance, and associated tumor cell functions of family with sequence similarity 111 member B in pancreatic adenocarcinoma

Abstract: Backgroud Among digestive tract tumors, pancreatic adenocarcinoma (PAAD) has a high degree of malignancy. Therefore, it is important to search for pancreatic adenocarcinoma‐related differential genes and new oncogene therapeutic targets for early diagnosis, treatment, and prognosis of pancreatic adenocarcinoma. Aims This study aims to investigate the expression and clinical significance of Family with sequence similarity 111 member B (FAM111B) in PAAD. Materials & Methods Bioinformatics was used to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Knockdown of CENPN resulted in suppressed cell growth, migration, and invasion of PAAD cells, whereas upregulation of CENPN significantly promoted cell proliferation, invasion, and migration. As the p53 signaling pathway is known to be related to the pathogenesis of PAAD [12,41], we analyzed the possible effects of CENPN in combination with this pathway. Western blot analysis showed that downregulation of CENPN in PAAD cells upregulated the expression of MDM2 and downregulated the expression of p53 and its downstream target p21, indicating that CENPN may play a role in regulating the P53 pathway in PAAD.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of CENPN resulted in suppressed cell growth, migration, and invasion of PAAD cells, whereas upregulation of CENPN significantly promoted cell proliferation, invasion, and migration. As the p53 signaling pathway is known to be related to the pathogenesis of PAAD [12,41], we analyzed the possible effects of CENPN in combination with this pathway. Western blot analysis showed that downregulation of CENPN in PAAD cells upregulated the expression of MDM2 and downregulated the expression of p53 and its downstream target p21, indicating that CENPN may play a role in regulating the P53 pathway in PAAD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xiang and colleagues found that FAM111B was lowly expressed in papillary thyroid cancer (PTC) tissues, leading to poor prognosis in PTC patients 4 . In addition, the over‐activation of FAM111B in pancreas, lung, cervix and breast increased the risk of related‐cancer 5–9 . Boldanova et al revealed that FAM111B was highly expressed in the tumor region of HCC patients and could be used as a biomarker for HCC patients treated with transarterial chemoembolization 10 .…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, the over-activation of FAM111B in pancreas, lung, cervix and breast increased the risk of related-cancer. [5][6][7][8][9] Boldanova et al revealed that FAM111B was highly expressed in the tumor region of HCC patients and could be used as a biomarker for HCC patients treated with transarterial chemoembolization. 10 Therefore, the course of HCC may have an inseparable relationship with FAM111B.…”
mentioning
confidence: 99%